Predicting the psychological and physiological prognosis of cardiac rehabilitation patients - Feldner-Busztin, Adrienne (My University, 1995)
The large percentage of deaths attributed to recurrent Coronary Heart Disease (CHD) has generated a search for behavioural and psychological factors which mitigate the consequences of CHD. An aim of the present thesis is to extend this search by identifying factors which predict prognosis fer recovery from CHD. Two key factors seen to influence prognosis are aerobic exercise and Type A behaviour. Extant research into the role of exercise has been hindered by methodological weaknesses. As a consequence, the precise means by which exercise influences CHD patients' psychological and physiological strain remains unclear. Similarly, the Type A literature has been flawed by the inaccurate conceptualisation and measurement of Type A behaviour as a global, and 110t a multidimensional, construct. Research which has examined the multidimensional nature of Type A behaviour has been restricted to low risk samples. Thus, a further aim. of the present research is to examine ; prognostic role of exercise and Type A components within the context of cardiac rehabilitation. In achieving this aim, three studies are conducted. [Abbreviated Abstract. Open document to view full version]
Thesis submitted to the Faculty of Arts, University of the Witwatersrand, for the degree of Doctor of Philosophy Johannesburg 1995
Keywords: Heart--Diseases--Patients--Rehabilitation; Coronary heart disease--Psychological aspects; Type A behavior; Medicine and psychology